Frost heave and thaw consolidation modelling. Part 2: One-dimensional thermohydromechanical (THM) framework - Yu, Fan; Guo, Peijun; Lai, Yuanming; Stolle, Dieter (NRC Research Press (a division of Canadian Science Publishing), 2020)
This paper presents a thermohydromechanical framework to model frost heave and (thaw) consolidation simultaneously, in which effective and total stresses are taken as the stress variables for unfrozen and frozen soils, respectively. “Effective (total) stresses – void ratio – permeability” relations are proposed to interpret the frost heave behavior of soil in different cooling modes, (thaw) consolidation processes, and changes in key parameters induced by freeze–thaw cycles. The water flux function proposed by Yu et al. in a companion paper is used to calculate frost heave in the frozen zone and to determine the moving boundary of the unfrozen zone during thaw consolidation. Compared with conventional methods, two other modifications are made to characterize the effect of residual stress and the influence of freeze–thaw cycling on permeability in the thaw consolidation analysis. After the governing equations developed in Lagrangian coordinates are implemented in a finite-element system, the framework is firstly verified by a comparison with both small- and large-strain thaw consolidation theories, in terms of simulating a semi-infinite thaw consolidation case, and is then examined with a focus on the three modifications one-by-one. Following that, the framework is assessed by two numerical examples that reasonably reproduce the freeze–thaw cycling processes in both seasonal frost and permafrost regions. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.